CIRO ALEGRIA, SEGÚN HENRY BONNEVILLE - Dealune Gazeau, Ghislaine (2010)
This article intends to present a portrait of Ciro Alegria and his work, from the perspective of the French scholar Henry Bonneville. This critical reflections developed from studying the work of the Peru, an writer, but also their friendship with him, using as key material, correspondence exchanged between them. The outcome of the Bonneville approach to the work of Joy, it appears that French critic's admiration for the Peruvian writer, not only in terms of artistic quality, but also his qualities as an intellectual and a man committed to his country.